Sistem Pakar Untuk Mendiagnosa Penyakit Pada Ibu Hamil Menggunakan Metode Depth First Search Berbasis Web - Sari, Eva Miftaviana; , Hernawan Sulistyanto, S.T.,M.T (2017)
Become a mother is not an easy thing because there will be pregnancy period and giving birth. However, we often hear that many woman are getting married and having pregnant in young age. Whereas, having pregnant in a young age is more risky to get a disturbance. It is not only because of the age factor, but also about the less knowledge about pregnancy. In the field of health, there is an artificial aptness called Expert System. It is a computer system that uses knowledge, fact, and reasoning technique in problem solving that usually solved by an expert in his field/area. This research uses Depth First Search method that will do a deeply investigation based on the fact that will be given by the user. The aim of this research is for helping the pregnant mom to diagnose the disease while pregnancy without meet the expert. The data are symptom, disease/illness, and solution. The result of this research is an expert system to diagnose pregnancy disease. Based on the trial toward the society, total interpretation percentage is 86,88% which is show that the society really agree with the application of expert system. Then 91,4% of total interpretation percentage related to the accuranteness of the data used.